2021
DOI: 10.1002/cpe.6266
|View full text |Cite
|
Sign up to set email alerts
|

A graphical processing unit‐based parallel hybrid genetic algorithm for resource‐constrained multi‐project scheduling problem

Abstract: In this article, we present a parallel graphical processing unit (GPU)-based genetic algorithm (GA) for solving the resource-constrained multi-project scheduling problem (RCMPSP). We assumed that activity pre-emption is not allowed. Problem is modeled in a portfolio of projects where precedence and resource constraints affect the portfolio duration. We also assume that the durations, availability of resources are deterministic and portfolio has a static nature. The objective in this article is to find a start … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The hybrid algorithm was applied to achieve the priority relationship of different problems in the project. The research results indicated that the hybrid algorithm improved the scheduling efficiency for multiple projects [6]. Su, Bentao et al introduced a hybrid genetic algorithm in job scheduling to reduce resource constraints and fully utilize resources.…”
Section: Related Workmentioning
confidence: 99%
“…The hybrid algorithm was applied to achieve the priority relationship of different problems in the project. The research results indicated that the hybrid algorithm improved the scheduling efficiency for multiple projects [6]. Su, Bentao et al introduced a hybrid genetic algorithm in job scheduling to reduce resource constraints and fully utilize resources.…”
Section: Related Workmentioning
confidence: 99%
“…To solve that weakness of GA, we propose GA based on subpopulation. This approach is adopting mechanism of parallel GA with the population that is naturally divided into a number of sub-populations that evolve and converge with a significant independence level [30]. Parallel GA can improve computational efficiency over classical GA.…”
mentioning
confidence: 99%